Decompensation of β-Cells in Diabetes: When Pancreatic β-Cells Are on ICE(R) - Roberto Salvi; Amar Abderrahmani (Journal of Diabetes Research)
Insulin production and secretion are temporally regulated. Keeping insulin secretion at rest after a rise of glucose prevents exhaustion and ultimately failure of β-cells. Among the mechanisms that reduce β-cell activity is the inducible cAMP early repressor (ICER). ICER is an immediate early gene, which is rapidly induced by the cyclic AMP (cAMP) signaling cascade. The seminal function of ICER is to negatively regulate the production and secretion of insulin by repressing the genes expression. This is part of adaptive response required for proper β-cells function in response to environmental factors. Inappropriate induction of ICER accounts for pancreatic β-cells dysfunction and ultimately death elicited by chronic hyperglycemia, fatty acids, and oxidized LDL. This review underlines the importance of balancing the negative regulation achieved by ICER for preserving β-cell function and survival in diabetes.